Respuesta :

Answer:

(F-G)(x) = -1

Step-by-step explanation:

The notation (F - G)(x) means to subtract each function when x = 6. According to the sets when x = 6 then F is (6,8) and G is (6,9). To subtract the functions, subtract their output values. (F-G)(x) = 8 - 9 = -1.

Step-by-step explanation:

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

[tex]f \times g = (2 \: , \:4 \times 5) \: , \: (4 \: , \: 6 \times 7) \: , \: (6 \: , \: 8 \times 9) \\ [/tex]

[tex]f \times g = (2 \: , \: 20) \: , \: (4 \: , \: 42) \: , \: (6 \: , \: 72) \\ [/tex]

_________________________________

Thus ;

[tex](f \times g)(2) = 20[/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️